2018
DOI: 10.1002/pro.3388
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating structure and acyl donor sites of a physiological transglutaminase substrate from Streptomyces mobaraensis

Abstract: Transglutaminase from Streptomyces mobaraensis (MTG) has become a powerful tool to covalently and highly specifically link functional amines to glutamine donor sites of therapeutic proteins. However, details regarding the mechanism of substrate recognition and interaction of the enzyme with proteinaceous substrates still remain mostly elusive. We have determined the crystal structure of the Streptomyces papain inhibitory protein (SPI ), a substrate of MTG, to study the influence of various substrate amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…TAMP inhibitory activity and glutamine accessibility for MTG are obviously counter‐regulated functions of SSTI and raise the question of how a more extended variant may influence SSTI. The result confirmed that MTG‐reactive glutamines are preferably located in flexible protein regions, especially at the terminal ends . MTG‐mediated side‐chain hydrolysis, however, is most likely not the reason for loss of reactive glutamines in the course of S. mobaraensis growth as hypothesized earlier , but successive removal of the N‐terminal extension peptide.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…TAMP inhibitory activity and glutamine accessibility for MTG are obviously counter‐regulated functions of SSTI and raise the question of how a more extended variant may influence SSTI. The result confirmed that MTG‐reactive glutamines are preferably located in flexible protein regions, especially at the terminal ends . MTG‐mediated side‐chain hydrolysis, however, is most likely not the reason for loss of reactive glutamines in the course of S. mobaraensis growth as hypothesized earlier , but successive removal of the N‐terminal extension peptide.…”
Section: Resultssupporting
confidence: 78%
“…Contrary to SSI and many SIL proteins, SSTI contains two adjacent glutamine residues that represent the most probable glutamine donor sites for cross‐linking by transglutaminase (MTG). Both residues, located in the SSTI extension peptide, obviously exhibit the required degrees of freedom to enter the MTG active core .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While failure of Sm-MTG to label Gln-129 and Gln-176 may be the result of backbone interaction and the occurrence of charged and bulky residues in close vicinity [21,40,41], the access to Gln-62 and Gln-65 was most likely caused by a largely disordered N-terminal D 1-50 -Sm-SrtE2 peptide (Table S1). While failure of Sm-MTG to label Gln-129 and Gln-176 may be the result of backbone interaction and the occurrence of charged and bulky residues in close vicinity [21,40,41], the access to Gln-62 and Gln-65 was most likely caused by a largely disordered N-terminal D 1-50 -Sm-SrtE2 peptide (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the evident success of mTG applications in diverse fields, the physiological role of this enzyme in its host S. mobaraensis is barely understood. Nevertheless, over the past decades the reactivity of glutamine sites within intrinsic substrate proteins have been thoroughly investigated . Our recent research revealed a novel recognition sequence for microbial transglutaminase that was derived from its natural substrate dispase autolysis‐inducing protein (DAIP).…”
Section: Introductionmentioning
confidence: 99%